(untitled) - Starr, Cecie (Australia, 2005)
Cecie Starr is the most successful author in non-majors biology because of her clear and engaging writing, trend-setting art, and unparalleled student and instructor media. Now in her brief NEW text, Starr creates in fewer than 500 pages a friendly, issues-oriented book with enormous instructional power. Integrating visuals from the book and accompanying media, Starr supports student mastery throughout and encourages students to make judgments about biology-related issues just as they will as citizens, voters, parents, employees, and consumers. While this brief book omits physiology coverage, it covers all other topics. The pedagogical focal points of each chapter are "Read Me First!" diagrams that introduce concepts before students read the longer text discussions. These visual previews, featuring annotated art presented in clearly numbered steps, make the subsequent text discussions more accessible. To solidify understanding, a narrated animation of each diagram appears on the free Student CD-ROM. "The Big Picture" on every chapter-opening page is a visual overview of the chapter's key concepts and is enhanced by a fully narrated, "mini-lecture" movie on the CD-ROM. The free Student CD-ROM provides access to BiologyNow, a powerful diagnostic learning tool that helps students assess their unique study needs through pretests and personalized learning plans. An "Impacts and Issues" opens each chapter focusing students on a key biology-related societal issue. Revisited throughout the chapter, this unfolding case study illustrates the chapter's biological concepts. Each chapter's "How Would You Vote?" feature asks students to consider biology-related news topics, gather and evaluate pro/con information, apply knowledge, then cast a vote on the Web. Students can see how peers in their state and across the nation voted. For additional facts and perspectives on each side of the issue, instructors can assign readings from the online Opposing Viewpoints
Keywords: Biology; Textbooks